Is Countermovement Jump Height and One Repetition Maximum Back Squat Associated With the Peak Force of a Front Kick With and Without Carried Load? - Oláh, Vladan; Třebický, Vít; Maleček, Jan; Michalička, Vladimír; Wąsik, Jacek; Vágner, Michal (Journal of strength and conditioning research, 2025)
Oláh, V, Třebický, V, Maleček, J, Michalička, V, Wąsik, J, and Vágner, M. Is countermovement jump height and one repetition maximum back squat associated with the peak force of a front kick with and without carried load? J Strength Cond Res 39(8): 880-889, 2025-The front kick is a fundamental technique used in self-defense and hand to hand combat. This study aimed to test whether front kick performance, both with and without a 30-kg carried load, can be effectively estimated or tracked through commonly available testing procedures such as the countermovement jumps (CMJ) and one repetition maximum back squat (1RM BS). In 2 testing sessions, 21 male participants (mean age = 22.7 years, SD = 1.9) performed 1RM BS, 5 front kicks peak force (FK) without and with 30-kg carried load (FK30), and 3 CMJ without and with 30-kg carried load (CMJ30). A force plate measured the peak force ( N ) of the FK and FK30 and the height (cm) of the CMJ and CMJ30. Statistically significant correlations were found between CMJ and FK ( r = 0.55 [0.225-1], p = 0.005) and CMJ and 1RM BS ( r = 0.54 [0.219-1, p = 0.005]). Carried load reduced both CMJ height by 61% ( d = 3.35 [2.543-∞], p < 0.001) and FK peak force by 23% ( d = 1.33 [0.828-∞], p < 0.001), compared without load condition. A regression model using 1RM BS and CMJ explained 31.5% of FK variance, with only the height of CMJ being statistically significantly associated, β = 0.626, p = 0.015. The study demonstrates that although there is a relationship between explosive power and maximum strengths, FK is more related to CMJ height than 1RM BS. From a practical standpoint, the study suggests that explosive power shows a better association with the FK than the maximal strength. Thus, training programs focused on lower limb explosive power could allow athletes and military personnel to achieve higher FK. Combat sports trainers and hand-to-hand combat instructors may thus consider accordingly updating their training schemes, emphasizing plyometrics and other explosive training methods for enhancing the peak force of kicks.
Keywords: martial arts; dospělí; strength; self-defense; biomechanika; Movement; Humans; pohyb; Athletic Performance; sportovní výkon; mladý dospělý; Resistance Training; performance; odporový trénink; Weight-Bearing; mužské pohlaví; Muscle Strength; Adult; hand to hand combat; training; Weight Lifting; zatížení muskuloskeletálního systému; svalová síla; lidé; kosterní svaly; vzpírání; Muscle, Skeletal; Male; Young Adult; Biomechanical Phenomena